Efeito de uma sessão de treinamento com haste oscilatória na ativação dos músculos estabilizadores da escápula em indivíduos assintomáticos com e sem discinese escapular - Serrão, Ricardo José Tecchio (2017)
Introduction: The change in the normal pattern of scapular movement is termed scapular dyskinesis and is strongly related to pathologies of the joint complex of the shoulder. The hyperactivation of upper trapezius fibers (UT) in concomitant with low activation of the inferior fibers (LT) and the serratus anterior (SA) are considered as the main factors that lead to scapular dyskinesis. Previous studies have demonstrated that exercises with oscillatory pole promote greater activation of the scapular muscles when compared to traditional resistances, such as free weight and elastic band. The oscillatory pole was also able to produce a UT / LT ratio of less than 1, which is considered to be the ideal for training the periscapular muscles. In this regard, it is suggested that oscillatory pole training may result in a rebalancing of the activation of the stabilizing musculature of the scapula. However, it is unknown the effect of a training protocol with oscillatory pole in the activation of the periscapular muscles. Objective: To analyze the effect of a single session of oscillatory pole training on the electromyographic activation (EMG) of the periscapular muscles in asymptomatic individuals with and without scapular dyskinesis. Methods: Thirty six healthy young adults were divided into two groups: the dyskinesis group (DG, n = 18) and Control group (CG, n = 18). For eligibility criteria, volunteers could not be involved in treatment for shoulder dysfunction, present injury, pain and / or surgery for the same 3 months prior to the research and be able to perform the proposed exercises. The EMG activation of the UT, LT and SA muscles were measured by a telemetry data acquisition system with a sampling frequency of 1000 Hz, a common rejection ratio of 90 dB and a total gain of 2000 times during the scaption movement. The speed of the scaption movement was standardized by a metronome programmed at 23 bpm. The evaluation was performed before and after the training session with the oscillatory pole. The exercise protocol was composed of six exercises, performed in three sets of 30 seconds each, with the execution speed standardized at 300 bpm (5 Hz). The data were analyzed through MATLAB software for the creation of the linear envelope. Thus, the EMG signal was filtered by a Butterworth bandpass filter of 20-500 Hz, rectified by the whole wave method and smoothed by a 4th order Butterworth lowpass filter with a cutoff frequency of 6 Hz. The mean of the linear envelopes was normalized by the mean of the maximum voluntary isometric contractions. Two-way repeated measures were used for statistical analysis. Results: Activation of the UT muscle was 87.9% higher in DG compared to CG. On the other hand, the LT muscle presented 14.7% greater EMG activation after training compared to before. The ratio between UT and SA muscles was 107.7% higher for DG compared to CG. Conclusion: Asymptomatic individuals with dyskinesis present, in addition to greater activation of the TS muscle, high TS / SA ratio compared to volunteers without dyskinesis. The oscillatory rod training was able to increase the activation of the TI muscle.